Synthesizing Highly Crystalline Self-Standing Covalent Organic Framework Films through a Homogeneous–Floating–Concentrating Strategy for Molecular Separation - He, Yasan; Lin, Xiaogeng; Zhou, Yanmei; Chen, Jian Hua; Guo, Zhiyong; Zhan, Hongbing (Chemistry of materials, 2021)
Covalent organic frameworks (COFs) have emerged as highly promising membrane materials owing to their intrinsic, tunable, and uniform pores. Due to their poor processing ability, the grand challenge for fabricating a COF film is to assemble COF crystallites into a membrane form. In addition, low crystallinity remains one of the major concerns for COF films. Herein, we report a “homogeneous–floating–concentrating” strategy for synthesizing highly crystalline self-standing COF films under mild conditions. This strategy takes advantage of a homogeneous synthesis and utilizes the slow concentration of a homogeneous reaction solution by solvent extraction and osmotic pressure to motivate the condensation reaction and push the assembly of COF crystallites to form compact films. Highly crystalline COFs were formed from the beginning of the reaction, overcoming the time mismatch between polymerization and crystallization. This strategy produced a series of self-standing COF films with superior crystallinity and porosity, better than corresponding COF films or powders reported in the literature. We synthesized a COF film with an unprecedentedly high surface area (3251 m2 g–1). These COF films exhibited outstanding permeance both for organic solvent and dye solutions along with excellent selectivity. A prominent instance is the TBDH film, which displays superior rejection (>99.9%) to Congo red solution, and unprecedented acetone and hexane permeances of 8939 and 9889 L m–2 h–1 MPa–1, respectively.